Piston rings

JP7637597B2Active Publication Date: 2025-02-28NTN CORP
-1 Cites 0 Cited by

Patent Information

Application Number
JP2021131224
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-03
Filing Date
2021-08-11
Publication Date
2025-02-28
Estimated Expiration
2041-08-11
Patent Text Reader

Abstract

To provide a piston ring excellent in abrasion resistance, which hardly causes abrasion damage to a cylinder.SOLUTION: A piston ring 1 used in a reciprocating type compressor for compressing gas is made of resin composition with polyether ether ketone resin as a main component. The melting viscosity of the polyether ether ketone resin in a shear rate of 1000 / s and a temperature of 400°C is 200-550 Pa s by a determination method based on ISO 11443. The resin composition contains 5-25 vol.% of carbon fiber and 5-25 vol.% of solid lubricant to the entire resin composition. The solid lubricant is at least one selected from PTFE resin and black lead.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a piston ring for a reciprocating compressor that compresses gas, and more particularly to a piston ring for a reciprocating compressor for hydrogen gas used in hydrogen stations. [Background technology]

[0002] Generally, a reciprocating compressor has a structure including a piston and a cylinder, and is used to compress a fluid by reciprocating the piston relative to the cylinder. In such a reciprocating compressor, an annular piston ring has been used for sealing the fluid in the gap between the piston and the cylinder. The piston ring is fitted in an annular groove provided in the piston. In this case, the outer circumferential surface of the piston ring contacts the inner circumferential surface of the cylinder, and the side surface of the piston ring contacts the side surface of the annular groove, thereby sealing the fluid.

[0003] In recent years, reciprocating compressors are also used as reciprocating compressors for hydrogen gas at hydrogen stations. In the reciprocating compressor for hydrogen gas, the compression mechanism of the compressor is used under severe conditions because it is necessary to compress hydrogen gas to the filling pressure for fuel cell vehicles. Therefore, the piston rings used in the reciprocating compressor for hydrogen gas are required to have further improved pressure resistance, heat resistance, sealing properties, wear resistance, and the like.

[0004] As such piston rings, resin piston rings with improved wear resistance are known. For example, Patent Document 1 describes a resin piston ring in which the total amount of polytetrafluoroethylene (PTFE) resin and one of polyether ether ketone (PEEK) resin and polyimide (PI) resin is 50 mass% or more of the total, and which does not contain polyphenylene sulfide (PPS) resin. Patent Document 1 states that by setting the tensile strength of the piston ring to a range of more than 15 MPa and less than 100 MPa, the piston ring can maintain its sealing performance for a longer operating period than piston rings outside that range.

[0005] Patent Document 2 describes a resin piston ring that is provided on one of the piston member and the cylinder liner and slides relative to the other member (the sliding member). Patent Document 2 describes that the replacement life of the piston ring due to wear can be extended by forming an amorphous carbon film on the sliding surfaces of both the piston ring and the sliding member. Note that the amorphous carbon film has a higher carbon content in the surface portion than in the inner portion. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-180600 A [Patent Document 2] Patent No. 6533631 Summary of the Invention [Problem to be solved by the invention]

[0007] In the above Patent Document 1, the material of the piston ring, that is, the blending ratio of each of the PTFE resin and the PEEK resin, and the blending ratio of each of the PTFE resin and the PI resin, etc. are not considered. In addition, Patent Document 2 describes that PTFE resin, PEEK resin, PI resin, etc. are used as the resin of the piston ring, and that, for example, PPS resin, molybdenum disulfide, etc. are blended as additives. However, the blending ratio, etc. are not considered. Therefore, it is considered that there is room for improving the wear resistance by examining the blending of the resin piston ring. In addition, it is desirable to be able to improve the wear of the mating material due to the sliding between the piston ring and the mating material such as the cylinder.

[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a piston ring which has excellent wear resistance and causes less wear damage to a cylinder. [Means for solving the problem]

[0009] The piston ring of the present invention is a piston ring used in a reciprocating compressor that compresses gas, characterized in that the piston ring is made of a resin composition containing PEEK resin as a main component, and the melt viscosity of the PEEK resin at a shear rate of 1000 / s and a temperature of 400°C is 200 Pa·s to 550 Pa·s as measured by a method conforming to ISO 11443. Note that the melt viscosity here refers to the melt viscosity of the PEEK resin alone, and is different from the melt viscosity of the resin composition. In addition, in the present invention, "gas" is a concept that means a general gas, and includes gaseous fuels and the like.

[0010] The resin composition is characterized in that it contains 5 volume % to 25 volume % of carbon fiber and 5 volume % to 25 volume % of a solid lubricant relative to the entire resin composition, and the solid lubricant is at least one selected from PTFE resin and graphite.

[0011] The carbon fibers have an average fiber length of 20 μm to 200 μm.

[0012] The present invention is characterized in that the reciprocating compressor is a reciprocating compressor for compressing hydrogen gas, and in that the resin composition does not contain a PPS resin.

[0013] The piston ring is a heat-treated product of an injection-molded article of the resin composition, and is characterized by having a lower content of sulfur atoms than the injection-molded article.

[0014] The piston ring is characterized in that it has an endothermic peak due to thermal history in the range of 150° C. to 330° C. during the temperature rise process in differential scanning calorimetry.

[0015] The piston ring is characterized in that the content of sulfur atoms is 250 ppm or less. Effect of the Invention

[0016] The piston ring of the present invention is made of a resin composition containing a PEEK resin as a main component, and the melt viscosity of the PEEK resin at a shear rate of 1000 / s and a temperature of 400°C is 200 Pa s to 550 Pa s, as measured by a measurement method in accordance with ISO 11443. Therefore, the piston ring has excellent abrasion resistance under reciprocating sliding conditions and causes little abrasion damage to the mating material.

[0017] The resin composition contains 5 volume % to 25 volume % of carbon fiber and 5 volume % to 25 volume % of solid lubricant (at least one selected from PTFE resin and graphite) relative to the entire resin composition, so that the resin composition has excellent friction and wear characteristics even in a compressor that does not use a lubricant such as oil.

[0018] Since the carbon fibers are short fibers with an average fiber length of 20 μm to 200 μm, wear damage to the mating material can be further reduced.

[0019] Here, in a reciprocating compressor for hydrogen gas, sulfur components contained in the piston ring may be gasified during the compression process and may be mixed into the compressed gas (hydrogen gas). If such compressed gas is filled into a fuel cell vehicle, it may have a detrimental effect on the fuel cell. In contrast, since the resin composition does not contain PPS resin, it is possible to prevent sulfur components derived from PPS resin from being mixed into the compressed gas. Even though the piston ring of the present invention does not contain PPS resin, it is excellent in wear resistance and the like by using the above-mentioned resin composition, and is therefore particularly suitable for a compressor for hydrogen gas, which requires wear resistance under high temperature and pressure and non-lubricated conditions.

[0020] Furthermore, the piston ring is a heat-treated product of an injection molded product of a resin composition, and has a lower sulfur atom content than an injection molded product, so the amount of outgas containing sulfur atoms (sulfur-containing gas) generated in a hydrogen atmosphere is reduced, making it particularly suitable for reciprocating compressors for hydrogen gas. In addition, when the heat treatment is performed in the atmosphere, there is no need for heat treatment in a special atmosphere, such as a treatment of exposure to a hydrogen atmosphere (desulfurization treatment) as described in the above Patent Document 2, and therefore the cost is low. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a perspective view of an example of a piston ring of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view of an example of a reciprocating compressor using the piston ring of the present invention. [Diagram 3] FIG. 1 is a schematic diagram of a pin-on-disk testing machine. [Figure 4] 1 is a graph showing the relationship between the melt viscosity of PEEK resin and the specific wear rate. [Diagram 5] FIG. 1 shows the results of differential scanning calorimetry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present inventors have conducted extensive research in order to improve the wear resistance of piston rings in particular, and have found that when a PEEK resin is used as the base resin for piston rings, the wear resistance can be significantly improved by setting the melt viscosity of the base resin within a specific range. The present invention is based on this finding.

[0023] An example of the piston ring of the present invention and a reciprocating compressor to which the piston ring is applied will be described with reference to Fig. 1 and Fig. 2. Fig. 1 is a perspective view showing an example of the piston ring of the present invention. As shown in Fig. 1, the piston ring 1 is an annular body having a substantially rectangular cross section. The corners between the inner peripheral surface 1b of the ring and both side surfaces 1c of the ring may be chamfered in a straight line or curved line, and when the seal ring is manufactured by injection molding, a step that protrudes from the mold may be provided in the corresponding portion.

[0024] The piston ring 1 is a cut-type ring having one abutment 1a, and is fitted into the annular groove of the piston by expanding its diameter through elastic deformation. Since the piston ring 1 has the abutment 1a, the diameter of the piston ring 1 is expanded by gas pressure during use, and the outer circumferential surface 1d comes into close contact with the inner circumferential surface of the cylinder. The shape of the abutment 1a is not limited, and it can be a straight cut type or an angle cut type, but it is preferable to adopt a composite step cut type shown in FIG. 1 because of its excellent sealing properties. The piston ring of the present invention is not limited to a piston ring made of a single member as shown in FIG. 1, but may be a piston ring formed into a circular ring by combining a plurality of members.

[0025] FIG. 2 is a cross-sectional view of an example of a reciprocating compressor using the piston ring of the present invention. The compression mechanism 2 of the reciprocating compressor comprises a cylinder 3 and a piston 4, and the piston 4 is connected to a piston rod 5. A plurality of annular grooves for mounting the piston rings 1 are arranged on the outer circumferential surface of the piston 4, and the piston rings 1 are expanded in diameter by elastic deformation and are fitted into each annular groove. There is no particular limit to the number of piston rings mounted on the piston, and six seal rings are mounted in FIG. 2. Gas is introduced into a compression chamber 6, compressed by the reciprocating motion of the piston 4 relative to the cylinder 3, and then discharged to the outside.

[0026] In the present invention, the gas compressed by the reciprocating compressor is not particularly limited, and may be, for example, hydrogen gas. Reciprocating compressors for compressing hydrogen gas are installed in hydrogen stations and used for filling fuel cell vehicles and hydrogen engine vehicles with hydrogen gas.

[0027] The resin composition used in the piston ring of the present invention will be described below.

[0028] The piston ring of the present invention is made of a resin composition having a PEEK resin as a base resin. In the present invention, the melt viscosity of the PEEK resin at a shear rate of 1000 / s and a temperature of 400°C is 200 Pa·s to 550 Pa·s according to a measurement method conforming to ISO 11443. The melt viscosity is determined by the average molecular weight and molecular weight distribution of the PEEK resin, and generally, the higher the molecular weight, the higher the melt viscosity. The PEEK resin may be any that satisfies this range. As a commercially available product, for example, 380P, 450P, 650P, etc. manufactured by Victrex Japan Co., Ltd. can be used. If the melt viscosity is less than 200 Pa·s, the wear resistance is insufficient for a piston ring used in a reciprocating compressor. Also, if the melt viscosity exceeds 550 Pa·s, molding processing by injection molding becomes difficult, which is not preferable in terms of cost. The melt viscosity is preferably from 270 Pa·s to 550 Pa·s, more preferably from 350 Pa·s to 550 Pa·s, and even more preferably from 350 Pa·s to 500 Pa·s.

[0029] It is preferable that the PEEK resin has a small amount of residual diphenyl sulfone, which is used as a solvent during polymerization. If the amount of residual diphenyl sulfone is large, sulfur-containing gas (such as hydrogen sulfide (H2S)) is likely to be generated when the PEEK resin is used as a piston ring. In a reciprocating compressor for hydrogen gas, if sulfur components are mixed into the compressed hydrogen gas, this may cause a decrease in the performance of the fuel cell, so the piston ring is required to have a low content of sulfur atoms. Therefore, it is preferable that the amount of residual diphenyl sulfone in the PEEK resin is small. When the piston ring of the present invention is obtained by injection molding of a PEEK resin composition or by machining an injection molding material, the maximum temperature of the cylinder of the injection molding machine is preferably 380°C or higher, which is higher than the boiling point of diphenyl sulfone (379°C). In addition, the pellets of the PEEK resin composition used in injection molding may be mixed with recycled materials prepared by crushing spools and runners generated during injection molding. Since recycled materials have been subjected to heat history more times than virgin materials without recycling, mixing recycled materials is advantageous in terms of removing diphenyl sulfone.

[0030] The resin composition used in the present invention preferably contains 50% to 90% by volume of PEEK resin, more preferably 60% to 90% by volume, and even more preferably 70% to 80% by volume of PEEK resin based on the entire resin composition. In addition, the PEEK resin may be a mixture of multiple PEEK resins with different melt viscosities, but the melt viscosity of the entire mixture of PEEK resins must be 200 Pa s to 550 Pa s.

[0031] The resin composition preferably contains 5% to 25% by volume of carbon fiber relative to the resin composition. If the carbon fiber content is less than 5% by volume, it is difficult to obtain the effect of improving abrasion resistance, and if it exceeds 25% by volume, the melt viscosity of the resin composition becomes high, making it difficult to perform injection molding. The carbon fiber content is more preferably 10% to 20% by volume.

[0032] The average fiber length of the carbon fibers is not particularly limited, but short fibers of 20 μm to 200 μm are preferable. If the average fiber length is less than 20 μm, it is difficult to obtain the effect of improving wear resistance, and if it exceeds 200 μm, the carbon fibers broken during sliding tend to get into the sliding surface, and tend to damage and wear the cylinder, etc. Note that the average fiber length in this specification is a number average fiber length.

[0033] The carbon fiber to be blended in the resin composition may be either pitch-based or PAN-based, as classified by the raw material. The calcination temperature is not limited, and may be either a graphitized product calcined at a high temperature of 2000°C or higher, or a carbonized product calcined at about 1000 to 1500°C. Commercially available milled fibers that can be used in the present invention include pitch-based carbon fibers such as Kureha Corporation's KUREKA M-101S, M-101F, M107T, and M-201S. In addition, PAN-based carbon fibers include Teijin Limited's HT M800 160MU and HT M100 40MU, and Toray Industries, Inc.'s Torayca MLD-30 and MLD-300. Carbon fibers may contain sulfur as an impurity. In the case of pitch-based carbon fibers, the raw pitch contains sulfur as an impurity. In the case of PAN-based carbon fibers, sulfur may remain if sulfuric acid is used for surface treatment.

[0034] In addition, the resin composition preferably contains at least one of the solid lubricants selected from PTFE resin and graphite in a total amount of 5% to 25% by volume relative to the resin composition. If the total amount of the solid lubricant selected from PTFE resin and graphite is less than 5% by volume, it is difficult to obtain an improvement in friction and wear properties under non-lubricated conditions, and if it exceeds 25% by volume, the tensile elongation properties of the resin composition may be reduced. If the tensile elongation properties are reduced, the piston ring may break when it is expanded and installed in the annular groove of the piston. Therefore, it is more preferable that the amount of the solid lubricant is 10% to 20% by volume.

[0035] PTFE resin is a solid lubricant and can improve the friction and wear properties of the resin composition under non-lubricated conditions. As the PTFE resin, any of molding powder by suspension polymerization method, fine powder by emulsion polymerization method, and recycled PTFE may be used. In order to stabilize the fluidity of the resin composition, it is preferable to use recycled PTFE, which is difficult to be fibrous due to shear during molding and difficult to increase the melt viscosity. The recycled PTFE is a powder that has been heat-treated (has been subjected to a thermal history) and a powder that has been irradiated with gamma rays or electron beams. For example, there are types such as a powder obtained by heat-treating molding powder or fine powder, a powder obtained by further irradiating this powder with gamma rays or electron beams, a powder obtained by crushing a molding powder or fine powder compact, a powder obtained by irradiating gamma rays or electron beams thereafter, and a powder obtained by irradiating molding powder or fine powder with gamma rays or electron beams. There is also a type that is further heat-treated after irradiation with gamma rays or electron beams. The 50% particle size of the PTFE resin is not particularly limited, but it is more preferable to set it to 10 μm to 50 μm.

[0036] Examples of commercially available PTFE resins that can be used in the present invention include KTL-610, KTL-450, KTL-350, KTL-8N, and KTL-400H manufactured by Kitamura Co., Ltd., Teflon (registered trademark) 7-J and TLP-10 manufactured by Mitsui Chemours Fluoroproducts Co., Ltd., Fluon G163, L150J, L169J, L170J, L172J, L173J, and L182J manufactured by AGC Inc., Polyflon M-15 manufactured by Daikin Industries, Ltd., and Dyneon TF9205 and TF9207 manufactured by 3M Japan Ltd. In addition, the PTFE resin may be modified with a side chain group having a perfluoroalkyl ether group, a fluoroalkyl group, or other fluoroalkyl groups. Among the above, examples of PTFE resins irradiated with gamma rays or electron beams include KTL-610, KTL-450, KTL-350, KTL-8N, and KTL-8F manufactured by Kitamura Co., Ltd., and Fluon L169J, L170J, L172J, L173J, and L182J manufactured by AGC Inc.

[0037] Graphite is a solid lubricant, and can improve friction and wear properties under non-lubricated conditions, similarly to PTFE resin. In addition, either natural graphite or artificial graphite may be used as the graphite. The particle shape may be flaky, granular, or spherical, and any of these may be used. Examples of natural graphite include ACP manufactured by Nippon Graphite Industries Co., Ltd., and examples of artificial graphite include KS-6, KS-25, and KS-44 manufactured by Imerys GC Japan Co., Ltd. The 50% particle size of graphite is not limited, but is preferably 3 μm to 50 μm, and more preferably 10 μm to 30 μm. If it exceeds 50 μm, the tensile elongation properties of the resin composition may be reduced. If the tensile elongation properties are reduced, the piston ring may break when it is expanded and fitted into the annular groove of the piston. Both natural graphite and artificial graphite contain sulfur as an impurity.

[0038] The 50% particle size (D 50 ) is the particle size at which the cumulative value is 50% when the particle size distribution is a cumulative distribution, and can be measured, for example, using a particle size distribution measuring device that uses a laser light scattering method.

[0039] The resin composition may contain a combination of carbon fiber and the above-mentioned solid lubricant, or may contain only carbon fiber or only a solid lubricant.

[0040] Well-known resin additives may be added to the resin composition to the extent that the effect of the present invention is not impaired. Examples of additives include inorganic substances (mica, talc, calcium carbonate, boron nitride, etc.), whiskers (calcium carbonate, potassium titanate, etc.), colorants (carbon black, iron oxide, titanium oxide, etc.), and other resin components. The resin additives may contain sulfur as an impurity. For example, in carbon black, sulfur exists in a state of being bonded to polycyclic aromatic hydrocarbons.

[0041] In addition, a resin having a higher glass transition point than PEEK resin may be blended in the resin composition in an amount less than that of PEEK resin, to the extent that the effect of the present invention is not impaired. This makes it possible to suppress the decrease in elastic modulus in a range higher than the glass transition point (143°C) of PEEK resin. As such a resin, for example, a thermoplastic polyimide resin, a thermosetting polyimide resin, a polyamide-imide resin, a polyetherimide resin, etc. can be selected, and the blending amount thereof can be, for example, 1% by volume to 10% by volume with respect to the entire resin composition.

[0042] It is preferable that the carbon fiber, PTFE resin, graphite, and other additives blended in the resin composition used in the present invention do not intentionally contain sulfur atoms (excluding those contained as impurities). Specifically, it is preferable that the resin composition does not contain PPS resin or molybdenum disulfide. In addition, the content of sulfur atoms as impurities is more preferably 0.1 mass% or less, and particularly preferably 0.025 mass% (250 ppm) or less, based on the total amount (100 mass%) of the resin composition. The content of the sulfur atoms can be measured, for example, using inductively coupled plasma mass spectrometry (ICP-MS). A triple quadrupole inductively coupled plasma mass spectrometry (ICP-MS / MS), which can perform analysis with higher accuracy, may also be used. As a pretreatment method for analysis, for example, a method of filtering a decomposition liquid obtained by acid decomposition in a microwave sample pretreatment device and obtaining a supernatant as an analysis sample can be mentioned. The absence of sulfur atoms in the decomposition residue can be confirmed by a known analysis method such as a fluorescent X-ray analyzer.

[0043] In view of the above, a particularly preferred embodiment of the resin composition of the present invention is one in which the base resin is a PEEK resin having a melt viscosity of 270 Pa·s to 550 Pa·s at a shear rate of 1000 / s and a temperature of 400°C as measured by a method conforming to ISO 11443, the resin composition contains 5 vol% to 25 vol% of carbon fiber and 5 vol% to 25 vol% of solid lubricant (at least one selected from PTFE resin and graphite), and the carbon fiber has an average fiber length of 20 μm to 200 μm. Furthermore, the resin composition preferably contains 10 vol% to 20 vol% of carbon fiber and 10 vol% to 20 vol% of PTFE resin, based on the entire resin composition.

[0044] The materials constituting the resin composition can be mixed as necessary using a Henschel mixer, a ball mixer, a ribbon blender, or the like, and then melt-kneaded using a melt extruder such as a twin-screw kneading extruder to obtain pellets for molding. The carbon fiber, PTFE resin, graphite, and the above-mentioned resin additives can be added by side feeding when melt-kneading using a twin-screw extruder or the like. The pellets for molding can be used to mold piston rings by injection molding. Additional processing or full processing can be performed using an injection molding material to finish into a predetermined piston ring shape. The molding method can be appropriately selected from compression molding, injection molding, extrusion molding, and the like, and among these, injection molding is preferred.

[0045] The piston ring of the present invention is preferably heat-treated before or after injection molding. Specifically, the piston ring is preferably (1) an injection molded body obtained by injection molding using the above molding pellets that have been heat-treated in the pellet state, or (2) a heat-treated body obtained by heat-treating an injection molded body that has been injection molded using the above molding pellets. In this way, by carrying out heat treatment before or after injection molding, the content of sulfur atoms contained in the resin composition can be reduced. As a result, the amount of sulfur-containing gas generated in a hydrogen atmosphere can be reduced compared to a piston ring that has not been heat-treated.

[0046] The content of sulfur atoms in the piston ring of the above (1) or (2) is preferably 0.1 mass% or less, more preferably 0.05 mass% or less, further preferably 0.025 mass% (250 ppm) or less, and particularly preferably 0.020 mass% (200 ppm) or less, relative to the total amount (100 mass%) of the resin composition.

[0047] The timing of carrying out the heat treatment is not particularly limited, and may be any timing between obtaining the molding pellets and manufacturing the piston rings. For example, if it is after injection molding, the heat treatment may be carried out at the stage of the injection molding material, or may be carried out after the injection molding material is cut out by machining.

[0048] The maximum temperature of the heat treatment is preferably 150°C to 330°C (more preferably 200°C to 250°C). If the maximum temperature is less than 150°C, it is difficult to obtain the effect of reducing sulfur-containing gas, and if it exceeds 250°C, deformation is likely to occur when heat treatment is performed after injection molding. In addition, the temperature is more preferably higher than the use temperature of the piston ring, and more preferably 30°C or more higher than the use temperature. In addition, the time to hold at the maximum temperature is not particularly limited, but is, for example, 4 hours to 8 hours. This heat treatment is effective in reducing sulfur in the piston ring, and can reduce sulfur-containing gas generated during use of the piston ring in advance. In addition, when a filler containing sulfur as an impurity, such as carbon fiber, graphite, or carbon black, is blended into the PEEK resin composition, it is particularly effective in removing active sulfur contained therein in advance.

[0049] When a piston ring formed by injection molding or a piston ring machined from an injection molding material is subjected to the above-mentioned heat treatment and then subjected to differential scanning calorimetry (DSC), an endothermic peak (hereinafter referred to as an endothermic peak due to thermal history) appears in the temperature rise process, which is not observed without the heat treatment. The endothermic peak due to thermal history appears at a temperature equal to or slightly higher than the maximum temperature of the heat treatment (within +20°C), so that the maximum temperature of the heat treatment can be estimated. The piston ring of the present invention preferably has an endothermic peak due to thermal history in the range of 150°C to 330°C (preferably in the range of 200°C to 250°C) in the temperature rise process of the differential scanning calorimetry due to the above-mentioned heat treatment. In this case, the piston ring has an endothermic peak in the range of 150°C to 330°C in addition to the endothermic peak derived from the melting point (about 343°C) of the PEEK resin. The measurement by DSC can be performed, for example, under conditions of a temperature rise rate of 15°C / min and in nitrogen gas.

[0050] In addition, it is preferable to carry out the heat treatment in the air, which reduces costs since it does not require heat treatment in a special atmosphere such as exposure to a hydrogen atmosphere (desulfurization treatment). EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0052] Examples 1 to 6, Comparative Examples 1 and 2 Using the PEEK resin composition blended in the blending ratio (volume %) shown in Table 1, an injection molding material with a diameter of 8 mm x 20 mm was molded by injection molding. This was then heat-treated in air at a maximum temperature of 220°C for 4 hours, and then machined to produce a pin test piece with a diameter of 3 mm x 13 mm.

[0053] The raw materials used in the PEEK resin composition are shown below. The melt viscosities of PEEK-1 to PEEK-5 were measured at a shear rate of 1000 / s and a temperature of 400° C. by a measurement method conforming to ISO 11443. (1) PEEK-1 Victrex Japan Co., Ltd.: 90P (melt viscosity 90 Pa·s) (2) PEEK-2 Victrex Japan Co., Ltd.: 150P (melt viscosity 130 Pa·s) (3) PEEK-3 Victrex Japan Co., Ltd.: 380P (melt viscosity 300 Pa·s) (4) PEEK-4 Victrex Japan Co., Ltd.: 450P (melt viscosity 350 Pa·s) (5) PEEK-5 Victrex Japan Co., Ltd.: 650P (melt viscosity 500 Pa·s) (6)CF-1 Kureha Corporation: Kureka M201S (average fiber length 150 μm) (7)CF-2 Toray Industries, Inc.: Torayca MLD-30 (average fiber length 30 μm) (8)CF-3 Kureha Corporation: Kureka M107T (average fiber length 400 μm) (9)PTFE resin Kitamura Co., Ltd.: KTL-450 (50% particle size 22 μm) (10) Graphite Nippon Graphite Industries Co., Ltd.: CGB-20 (50% particle size 20 μm)

[0054] As shown in Table 1, a resin composition (not including graphite) consisting of only PEEK resin with a predetermined melt viscosity, carbon fiber, and PTFE resin was used in Examples 1 to 3 and Examples 5 to 6. Also, a resin composition consisting of only PEEK resin with a predetermined melt viscosity, carbon fiber, PTFE resin, and graphite was used in Example 4.

[0055] <Friction and wear test> A friction and wear test was performed on the obtained pin test pieces using a pin-on-disk tester shown in Fig. 3. As shown in Fig. 3, the test surfaces of the three pin test pieces 7 were pressed against the surface of a rotating disk 8 of the test machine with the following surface pressure, and the rotating disk 8 was rotated at room temperature. The specific test conditions are as follows, and the material of the rotating disk 8 is SUS304. Note that these test conditions are assumed to be the usage conditions of piston rings in a reciprocating compressor for hydrogen gas. (Test conditions) Circumferential speed: 4.8m / min Surface pressure: 4MPa Lubrication: None (dry) Temperature: room temperature Time: 50 hours

[0056] After the test, the change in height of the pin test piece 7 before and after the test was measured, and the specific wear rate was calculated from the average value of the three pieces. In addition, the wear damage of the mating material (rotating disk 8) was visually confirmed. The results are shown in Table 1. [Table 1]

[0057] As shown in Table 1, in Examples 1 to 6, the specific wear rate was 19 × 10 -8 mm 3 / (N·m)~79×10 -8 mm 3 The specific wear rates for Comparative Examples 1 and 2, which used PEEK resin with a melt viscosity of less than 200 Pa s, were 413 × 10 -8 mm 3 / (N·m), 200×10 -8 mm 3 / (N·m), which resulted in inferior abrasion resistance to Examples 1 to 6. Furthermore, in Example 5 (average fiber length of carbon fibers: 400 μm), slight abrasion damage was observed in the counter material.

[0058] FIG. 4 shows the relationship between the melt viscosity of PEEK resin and the specific wear rate for Examples 1 and 2, Example 6, and Comparative Examples 1 and 2 (combination of 10 volume % CF-1 and 10 volume % PTFE resin). As shown in FIG. 4, there was a tendency for the specific wear rate to increase sharply when the melt viscosity of PEEK resin fell below a certain level. In the present invention, by setting the melt viscosity of PEEK resin in the range of 200 Pa s to 550 Pa s, a piston ring with a small specific wear rate and excellent wear resistance is obtained.

[0059] The injection molding material used to prepare the pin test piece of Example 1 was subjected to quantitative analysis of sulfur atoms before and after heat treatment at a maximum temperature of 220°C for 4 hours. The injection molding material was freeze-pulverized and acid-decomposed in a microwave sample pretreatment device, and the decomposition liquid obtained was filtered, and the supernatant was obtained as an analysis sample. When this analysis sample was analyzed by ICP-MS / MS, the sulfur content was 220 ppm before heat treatment and 150 ppm after heat treatment. It was confirmed by a fluorescent X-ray analyzer that the decomposition residue did not contain sulfur atoms.

[0060] Separately, an injection molding material of a resin composition mainly composed of PEEK resin was heat-treated at a maximum temperature of 210°C for a holding time of 4 hours at the maximum temperature. An example of the results of differential scanning calorimetry (DSC) performed after heat treatment is shown in Figure 5. As shown in Figure 5, during the temperature rise process, an endothermic peak was observed at 223°C, which was not observed without heat treatment.

[0061] As described above, the piston ring of the above-mentioned embodiment has an endothermic peak due to thermal history in the range of 150° C. to 330° C. during the temperature rise process in differential scanning calorimetry, which corresponds to the maximum temperature in the heat treatment process. [Industrial Applicability]

[0062] The piston ring of the present invention is suitable for use as a piston ring in a reciprocating compressor that compresses gas, has excellent wear resistance, and causes little wear damage to the cylinder. In addition, since the generation of outgassing containing sulfur atoms can be reduced, the piston ring can also be used in a reciprocating compressor for hydrogen gas in which contamination by sulfur must be avoided. [Explanation of symbols]

[0063] 1. Piston ring 2. Compression mechanism 3 Cylinder 4 Piston 5 Piston rod 6 Compression Chamber 7-pin test strip 8 Rotating Disc

Claims

1. A piston ring for use in a reciprocating compressor for compressing hydrogen gas, comprising: The piston ring is made of a resin composition containing polyether ether ketone resin as a main component, The polyether ether ketone resin has a melt viscosity of 200 Pa s to 550 Pa s at a shear rate of 1000 / s and a temperature of 400°C, as measured by a method conforming to ISO 11443; The resin composition contains 5% by volume to 25% by volume of carbon fiber and 5% by volume to 25% by volume of a solid lubricant based on the entire resin composition, the solid lubricant is at least one selected from polytetrafluoroethylene resin and graphite, The carbon fiber is a PAN-based carbon fiber, and has an average fiber length of 20 μm to 200 μm.

2. 2. The piston ring according to claim 1, wherein the resin composition does not contain a polyphenylene sulfide resin.

3. 3. The piston ring according to claim 1, wherein the piston ring is a heat-treated body of an injection-molded body of the resin composition, and has a lower content of sulfur atoms than the injection-molded body.

4. 4. The piston ring according to claim 1, wherein the content of sulfur atoms in the piston ring is 250 ppm or less.

5. A piston ring used in a reciprocating compressor for compressing hydrogen gas, comprising: The piston ring is made of a resin composition containing polyether ether ketone resin as a main component, The polyether ether ketone resin has a melt viscosity of 200 Pa s to 550 Pa s at a shear rate of 1000 / s and a temperature of 400°C, as measured by a method conforming to ISO 11443; The resin composition contains 5% by volume to 25% by volume of carbon fiber and 5% by volume to 25% by volume of a solid lubricant based on the entire resin composition, the solid lubricant is at least one selected from polytetrafluoroethylene resin and graphite, The piston ring is a heat-treated product of an injection-molded product of the resin composition, and has a lower sulfur atom content than the injection-molded product, the sulfur atom content of the piston ring being 200 ppm or less.